Pengaruh Persepsi Harga, Kualitas Pelayanan, Lokasi, Brand Image Dan Kualitas Produk Terhadap Keputusan Pembelian Pada Pelanggan Minimarket” (Studi Pada Pelanggan Minimarket Swalayan Sauli Mart Kesamben). - Ratna Dewi Kartika Sari; Rois Arifin; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract This study aims to determine: (1) the effect of price perceptions on purchasing decisions on the saulimart kesamben supermarket, (2) the effect of service quality on the saulimart kesamben supermarket purchasing decisions, (3) the influence of location on the purchase decision on the saulimart kesamben supermarket, (4) the effect of brand image on purchasing decisions at saulimart kesamben supermarket, (5) the effect of consumer commitment on purchasing decisions on saulimart kesamben supermarket and (6) the effect of perceived price, service quality, location, brand image and consumer commitment on purchasing decisions on saulimart kesamben supermarket. This study uses a causal associative method using a quantitative approach. The population in this study are consumers who have made a purchase at Saulimart Kesamben. The sampling technique uses purposive sampling with a sample size of 190 people. Data collection techniques using questionnaires that have been tested for validity and reliability. Data analysis techniques using multiple regression. The results of this study indicate that: (1) price perceptions have a significant positive effect on purchasing decisions on saulimart kesamben supermarket customers as indicated by the value of t count> t table and significant <0.05; (2) service quality has a significant positive effect on purchasing decisions on saulimart kesamben supermarkets with t arithmetic> t table and significant <0.05; (3) location has a significant positive effect on Saulimart Kesamben's self-service purchasing decisions with a value of t arithmetic> T table and significant <0.05; (4) brand image has a significant effect on purchasing decisions on sauli mart supermarket customers with the value of t arithmetic> t table and significant <0.05; (5) consumer commitment has a significant positive effect on purchasing decisions on saulimart kesamben supermarkets with t arithmetic values> t table and significant <0.05 Keywords: Effect of Price, Service Quality, Location, Brand Image, Consumer Commitment, and Purchasing Decisions